On the Use of Issue Tracking Annotations for Improving Developer Activity Metrics. (20th January 2011) - Meneely, Andrew; Williams, Laurie
Abstract : Understanding and measuring how teams of developers collaborate on software projects can provide valuable insight into the software development process. Currently, researchers and practitioners measure developer collaboration with social networks constructed from version control logs. Version control change logs, however, do not tell the whole story. The collaborative problem-solving process is also documented in the issue tracking systems that record solutions to failures, feature requests, or other development tasks. We propose two annotations to be used in issue tracking systems: solution originator and solution approver. We annotated which developers were originators or approvers of the solution to 602 issues from the OpenMRS healthcare system. We used these annotations to augment the version control logs and found 47 more contributors to the OpenMRS project than the original 40 found in the version control logs. Using social network analysis, we found that approvers are likely to score high in centrality and hierarchical clustering. Our results indicate that our two issue tracking annotations identify project collaborators that version control logs miss. Thus, issue tracking annotations are an improvement in developer activity metrics that strengthen the connection between what we can measure in the project development artifacts and the team's collaborative problem-solving process.